A replication of the response‐restriction preference assessment. (19th July 2019) - Boyle, Megan A.; Curtis, Kaitlin S.; Forck, Kara L.; Fudge, Brittany M.; Speake, Heather N.; Pauls, Benjamin P.
Abstract: We replicated the response‐restriction (RR) preference assessment and compared results in terms of preference hierarchies to those from free‐operant and multiple stimulus without replacement (MSWO) formats with six children with autism spectrum disorders (ASDs). We also assessed social validity of each format with teachers and clinicians who work with children with ASDs. Complete hierarchies were produced in four of 18 assessments and with MSWO and RR formats only. Results of the social validity assessment varied across raters, with each preference assessment format receiving the highest rating from at least one rater. Results are discussed in terms of practical recommendations and relative to the preference assessment literature as a whole.